1,2-Dihydropentalenes from Fulvenes by [6 + 2] Cycloadditions with 1-Isopropenylpyrrolidine - Coşkun, Necdet; Ma, Jingxiang; Azimi, Saeed; Gärtner, Christian; Erden, Ihsan (Organic letters, 2011)
In situ generated acetone pyrrolidine enamine undergoes [6 + 2] cycloadditions with fulvenes to give 1,2-dihydropentalenes. This ring annulation method works particularly well with 6-monosubstituted fulvenes and is subject to steric hindrance at C-6 of the fulvene. On the basis of mechanistic studies, optimal conditions have been developed for a one-pot synthesis of 1,2-dihydropentalenes using catalytic amounts of pyrrolidine.